Prophetic Communication and the Formation of Pesantren Habitus: A Structural Functionalism Perspective - Andri Kurniawan; Sarifudin Sarifudin; Mohammad Alawi (Al-Insyiroh: Jurnal Studi Keislaman, 2026)
Communication errors often hinder relationship building, including in Pesantren (Islamic Boarding School). With various problems faced today, such as radicalism, violence, and sexual abuse, Islamic traditions need to be strengthened. The purpose of the research is to re-read the tradition (habitus) of Pesantren in Nurul Hakim Kediri and Hikmatusysyarief NWDI Narmada through the actualization of empathetic, persuasive, and communication ethics. This study uses qualitative-phenomenological methods through in-depth interview, observation, and documentation. Interviews were conducted with teachers, cottage caregivers, and several students. The limitation of observation carried out is the behavior, communication traditions of students, as well as the documents obtained from the pesantren. The results of the study show that the habitus of Pesantren today can be seen from the dynamics of adaptive attitudes towards modernization, applicable Pesantren regulations, and Pesantren habitus formed in the environment of the boarding school and madrasah. Prophetic communication in Pesantren is built through, first, empathetic communication, which is building emotional and affirmative relationships. Second, persuasive communication as an effort to influence mindsets and behaviors in learning and socializing. Third, communication ethics that are important to pay attention to in strengthening the habitus of Pesantren